Caracterización de los productores agroecológicos de la provincia Tungurahua para establecer estrategias de manejo fitosanitario en los cultivos de las asociaciones. - Lasluisa Cabascango, Elvia Daniela (2022)
This research was developed within the framework of the signing of the inter-institutional agreement between the Technical University of Cotopaxi, GIZ and PACAT of the province of Tungurahua. The objectives were framed in characterizing the Agricultural Production Units (UPAs), as well as the agricultural practices of all the active members of the associations that make up the PACAT, in addition, critical points and possible potentialities of the organizations were determined and, finally, , the relevant strategies were established in the phytosanitary management of crops. For the characterization, surveys were used, applied on site and analyzed with descriptive statistics to determine percentages of response frequencies. For the determination of critical points and potentialities, two statistical analyzes were applied: Natural Capital Amoeba and Principal Component Analysis. For the elaboration of the final proposal, the following were considered: the critical points found, the agroecological principles and the techniques related to their fulfillment, in addition, the pest and disease with the greatest economic impact on the main crop. It has been possible to identify 9 critical points, these being: work on the protection of water sources, carrying out botanical macerates, purchase of seeds and seedlings, pest and disease attacks and how they are controlled, activities aimed at protecting forests and native species present at the UPA. In addition, 5 potentialities are seen: 84% of the producers are dedicated to raising guinea pigs; 70% of the producers produce pastures, 49% of these are alfalfas; 76% of the producers practice the technique of alternating crops and 78% of the producers make bio-inputs. The research concludes with a final proposal that establishes a phytosanitary management for Bemicia tabasi (main pest) in tree tomato (main crop) and Bactericera cockerelli (major disease) in tree tomato.